1987
DOI: 10.1177/1077727x8701600101
|View full text |Cite
|
Sign up to set email alerts
|

Family Cash‐Flow Budgeting

Abstract: A budget process variable is developed to address three research questions con cerning family cash‐flow management: (1) how frequently is the formalized cash‐ flow budget used, (2) what are the characteristics of those families who tend to use it, and (3) what are the potential benefits associated with the use of a formal budget. The distribution for a formalized budget variable is reported for a repre sentative sample of Iowa families. The distribution is skewed with a dispropor tional large group of househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 4 publications
2
17
0
1
Order By: Relevance
“…Money managers who had higher household monthly income reported a higher level of satisfaction with their preparation for financial emergencies than did those with lower household monthly income. Titus et al (1989) and Beutler and Mason (1987) reported similar findings. The presence of insignificant coefficients for some input variables may indicate multicollinearity problems in the model (linear association between input variables).…”
Section: Predictors Of Satisfaction Withsupporting
confidence: 88%
See 3 more Smart Citations
“…Money managers who had higher household monthly income reported a higher level of satisfaction with their preparation for financial emergencies than did those with lower household monthly income. Titus et al (1989) and Beutler and Mason (1987) reported similar findings. The presence of insignificant coefficients for some input variables may indicate multicollinearity problems in the model (linear association between input variables).…”
Section: Predictors Of Satisfaction Withsupporting
confidence: 88%
“…Money managers who used a larger proportion of their income to pay installment debt were less likely to be satisfied with their preparation for financial emergencies. Several other researchers have found similar findings (see Beutler & Mason, 1987;Hira, 1987a;Titus et al, 1989).…”
Section: Predictors Of Satisfaction Withsupporting
confidence: 75%
See 2 more Smart Citations
“…Godwin (1990) has described the inadequacy of family financial management behaviors: Godwin and Carroll (1986) found that families, on average, engaged in fewer than 6 of 18 recommended financial management behaviors. As measured by Beutler and Mason (1987), fewer than 10% of families had high budget formality scores, including keeping written plans and records of expenditures, reviewing expenditures and using a planning horizon of one year or more. Almost 20% of their families never engaged in any of these practices and reported planning horizons of one day or less.…”
mentioning
confidence: 99%